2014
DOI: 10.3892/mmr.2014.2329
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide-pneumoperitoneum in rats reduces ischemia/reperfusion-induced hepatic apoptosis and inflammatory responses by stimulating sensory neurons

Abstract: Laparoscopic surgery induces a milder inflammatory response than open surgery, however, the precise mechanisms underlying this phenomenon remain to be elucidated. Our previous study demonstrated that stimulation of sensory neurons inhibited hepatic apoptosis and inflammatory responses in rats subjected to hepatic ischemia/reperfusion (I/R). Since carbon dioxide (CO2) has been demonstrated to stimulate sensory neurons, it was hypothesized that CO2‑pneumoperitoneum, as used in laparoscopic surgery, may attenuate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, apoptosis increased in high CO 2 pressure. [ 24 ] In experimental studies, it was shown that high IAP directly increased renal[ 25 ] and hepatic[ 26 ] cell apoptosis. In our study, the high ovarian apoptotic scores during pneumoperitoneum were also demonstrated by histpathological study, as clearly shown in Figure 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, apoptosis increased in high CO 2 pressure. [ 24 ] In experimental studies, it was shown that high IAP directly increased renal[ 25 ] and hepatic[ 26 ] cell apoptosis. In our study, the high ovarian apoptotic scores during pneumoperitoneum were also demonstrated by histpathological study, as clearly shown in Figure 2 .…”
Section: Discussionmentioning
confidence: 99%